Consequences and Drivers of Differentiated Environmental Regulation Policies on Hog Production in China: A Spatial Econometrics Approach - Zeng, Fang; Yan, Lingxiao; Tan, Ying (Frontiers in Environmental Science, 2022)
Using a spatial econometric approach and national prefecture-level hog inventory data, this paper analyzes the extent to which environmental regulation policies influence hog production in China, and obtained the following research results: (1) During the 12th Five-Year Plan period, environmental regulation policies will significantly reduce the output of the hog industry in highly regulated areas. (2) The specific policy commands from the central government targeting on livestock sector and a high share of agriculture in the economy will increase the stringency of the environmental regulation policies on hog production. (3) The COD emission reduction requirements also have a significant negative impact on major hog farming provinces, the results obtained from the main model are verified again. The results highlight the importance of a more flexible environmental decentralization regime in China and other developing countries for future reforms.